1974
DOI: 10.1042/bj1420327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lysine on gluconeogenesis from lactate in rat hepatocytes

Abstract: 1. In freshly prepared isolated rat liver cells there is a lag in gluconeogenesis from lactate. The magnitude of the lag increases with increasing lactate concentration. 2. The lag is virtually abolished by lysine. 3. A few other amino acids (tyrosine, arginine, asparagine, ornithine) and NH(4)Cl had effects similar to, but less pronounced than, lysine during the early stage of incubation. Lysine was unique in accelerating gluconeogenesis beyond the lag period. 4. The effects of the accelerators are not additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
2
1

Year Published

1975
1975
1994
1994

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 20 publications
8
58
2
1
Order By: Relevance
“…The rates of gluconeogenesis from lactate in isolated liver cells of fed pregnant rats showed a 3-4-fold increase at days 20, 21 and 22 of gestation when compared to the rates found in fed virgin rats ( fig.lB). It should be pointed out that the basal rates of ~u~oneogenesis observed in virgin rats are lower than those previously reported [ 18,19,22,24]. This difference is most likely due to the use in our experimental protocol of: (i) liver cells isolated from rats fed ad libitum, since starvation is well known to increase the gluconeogenic capacity of the liver 125,261; and (ii) an incubation medium that included glucose and half the concentration of lactate used by others, but that was designed with the purpose of simulating the physiological concentrations of both metabolites to which liver cells are exposed in vivo [ 11,141.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The rates of gluconeogenesis from lactate in isolated liver cells of fed pregnant rats showed a 3-4-fold increase at days 20, 21 and 22 of gestation when compared to the rates found in fed virgin rats ( fig.lB). It should be pointed out that the basal rates of ~u~oneogenesis observed in virgin rats are lower than those previously reported [ 18,19,22,24]. This difference is most likely due to the use in our experimental protocol of: (i) liver cells isolated from rats fed ad libitum, since starvation is well known to increase the gluconeogenic capacity of the liver 125,261; and (ii) an incubation medium that included glucose and half the concentration of lactate used by others, but that was designed with the purpose of simulating the physiological concentrations of both metabolites to which liver cells are exposed in vivo [ 11,141.…”
Section: Resultsmentioning
confidence: 59%
“…In our preparations, this effect was not observed; in fact, the rates of gluconeogenesis from L-lactate were linear during 40-50 min of incubation ( fig.lA). The existence of the lag period was explained by Cornell et al [22] by the precedence of the reoxidation of cytosolic NADH over giuconeogenesis, meaning that much of the oxaloacetate formed by the pyruvate carboxylase reaction has to be transferred 'twice' from the mit~hondria to the cytosol by the aspartate shuttle before being converted into phosphoenolpyruvate. The observed discrepancy could be explained on the basis of the previous hypothesis [22]: th?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies were in progress, Cornell et al (1974) reported a similar lag period in glucose synthesis from lactate by isolated rat liver cells which was significantly shortened by the addition of NH4CI, lysine and other amino acids. In their experiments, however, the lag phase was considerably longer (40min) than in our studies but appeared to lead to a similar decrease in the lactate/pyruvate ratio.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, although in this unmodified state they are a useful tool for demonstrating the consequences of limitation of shuttle capacity on metabolism [29], they do not accurately reveal the interactions of glycolysis and ethanol oxidation under physiological conditions where shuttle capacity is intact. During incubation the hepatocytes correct this deficiency in shuttle capacity over a period of 20-30 min [30, 361 but it can be rectified from the commencement of the incubation by inclusion of asparagine in the medium, since this restores shuttle capacity to normal [30]. Thus, if it is desired to examine the interactions of glycolysis and ethanol under physiological conditions, one approach is to employ asparagine-supplemented hepatocytes.…”
Section: The Fate Of Glucose Not Glycolysed In the Presence Of Ethanolmentioning
confidence: 99%